2000
DOI: 10.1080/01971520009349543
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Anti-Gm1 Ganglioside Antibodies in Patients with Neuropathy by a Novel Latex Agglutination Assay

Abstract: Highly elevated titers of serum anti-GM1 ganglioside antibodies are closely associated with multifocal motor neuropathy, but low titers are commonly present in normal individuals or other diseases. Current systems for measuring anti-GM1 antibodies utilize the enzyme-linked immunosorbent assay (ELISA), in which serum dilutions are tested for binding to excess antigen immobilized on the surface of microwells. The ELISA system, however, is relatively time consuming, labor intensive, and costly, in addition to bei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…Researchers and clinicians have also attempted to use immunosuppressants as a treatment, on the assumption that in ALS, as in many other neurodegenerative diseases, inflammation may be associated with disease propagation and therefore deleterious (39,40). Also, the presence of anti-ganglioside antibodies in ALS patients (41) has led some researchers to suggest that ALS is an autoimmune disease. However, there is no conclusive evidence for any of these hypotheses, and therapy with immunosuppressants, including whole-body irradiation, has failed to show any effect (42).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers and clinicians have also attempted to use immunosuppressants as a treatment, on the assumption that in ALS, as in many other neurodegenerative diseases, inflammation may be associated with disease propagation and therefore deleterious (39,40). Also, the presence of anti-ganglioside antibodies in ALS patients (41) has led some researchers to suggest that ALS is an autoimmune disease. However, there is no conclusive evidence for any of these hypotheses, and therapy with immunosuppressants, including whole-body irradiation, has failed to show any effect (42).…”
Section: Discussionmentioning
confidence: 99%
“…Since then, extensive studies have examined the sensitivity and specificity of anti-GM1 IgM antibody detection in MMN, related disorders and control populations(Adams et al, 1991;Kornberg et al, 1994;Lewis et al, 1982;Parry and Sumner, 1992;Pestronk, 1991), using a range of assay methodologies(Alaedini and Latov, 2000;Bech et al, 1994;Carpo et al, 1999;Chabraoui et al, 1993;Conrad et al, 2007;Escande-Beillard et al, 2002;Pukin et al, 2011;Ravindranath et al, 1994;Willison et al, 1999). Although no uniform consensus on methodology has been achieved, in part due to differences in defining patient populations and assay reproducibility, it is widely accepted that IgM antibodies to GM1 do occur in a significantly higher proportion of MMN cases compared with control groups(Baumann et al, 1998;Nobile-Orazio et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Antibodies to GM1 ganglioside were first identified in multifocal motor neuropathy (MMN) sera by Pestronk and colleagues almost 25 years ago [1]. Since then, extensive studies have examined the sensitivity and specificity of anti-GM1 IgM antibody detection in MMN, related disorders and control populations [2][3][4][5][6], using a range of assay methodologies [7][8][9][10][11][12][13][14][15]. Although no uniform consensus on methodology has been achieved, in part owing to differences in defining patient populations and assay reproducibility, it is widely accepted that IgM antibodies to GM1 do occur in a significantly higher proportion of MMN cases compared with control groups [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Considering the usefulness of the antibody assay for the diagnosis of GBS, it is of importance to develop a method that can be easily performed by clinicians. Alaedini and Latov reported the latex agglutination assay for detection of anti-ganglioside antibodies (15). In this issue, Irie et al reported the results of antiganglioside antibody assay by the use of the above method with some modifications and compared the results with those of ELISA (16).…”
mentioning
confidence: 99%